Foreign Investment, Domestic Savings, and Exchange Rates as Drivers of Per Capita Income and Financial Sector Development in OIC Countries - Garini, Fitri Ardiya; Majid, M. Shabri Abd.; Suriani, Suriani (Grimsa Journal of Business and Economics Studies, 2025)
This study examines the roles of foreign investment, financial sector development, domestic savings, and exchange rates on per capita income in 25 Organization of Islamic Cooperation (OIC) countries. A panel data regression model is applied to annual data from 2010 to 2022. The results indicate that foreign investment and domestic savings positively influence financial sector development, while the exchange rate has no significant effect. Additionally, both foreign investment and savings positively impact economic growth, whereas the exchange rate and financial sector have a negative effect. Based on these findings, it is recommended that the governments of the OIC-25 countries enhance the attractiveness of foreign investment through policies that foster a conducive investment climate and increase awareness and incentives for domestic savings. This approach would strengthen the financial sector and boost per capita income growth. The study suggests that while foreign investment and domestic savings can drive financial sector development and economic growth, exchange rate fluctuations and inefficient financial sector management can hinder increases in per capita income.